Usage pattern analysis of Beijing private electric vehicles based on real-world data. (15th January 2019) - Zhang, Xudong; Zou, Yuan; Fan, Jie; Guo, Hongwei
Abstract: Developing electric vehicles, as one of the most effective measures in constructing clean transportation, has been vigorously prompted by China's government recently through series of beneficial policies. Thus, both the sales and manufacturing of electric vehicles have witnessed prosperous growth in the last decade, especially in Beijing, whose pure electric vehicles ownership has exceeded 170, 000 by the end of 2017 and ranked first in China. However, large-scale deployment of electric vehicles may also bring about troublesome problems concerning the construction of charging infrastructure and stability of electric grid. A comprehensive analysis of usage pattern of electric vehicles, especially the majority for private usage, is useful in predicting the charging load and understanding the driving characteristics, thus guiding location of charging facilities and assisting energy management of electric grid. By collecting operational data of forty-one private electric vehicles with 33, 041 trips and 4738 charging events, sixteen characteristic parameters including charge consumption, state of charge before/after charging, single-trip distance, daily distance travelled, specific energy consumption, etc. are analyzed in detail. The analysis results are useful in facilitating charging infrastructures construction, management of state gird, evaluation of emerging vehicular technology and so forth in Beijing and even other metropolises with similar situation. Highlights: Operational data of 41 private electric vehicles in Beijing were collected. The usage pattern of Beijing private electric vehicles is investigated. Usage pattern of electric vehicles is related to drivers' daily routine. Inter-quartile range analysis is used to investigate the charging characteristics.